Tau-Mediated Dysregulation of Neuroplasticity and Glial Plasticity - Koller, Emily J.; Chakrabarty, Paramita (Frontiers in Molecular Neuroscience, 2020)
Inability of individual neurons to compensate for aging-related damage leads to gradual loss of functional plasticity in the brain accompanied by progressive impairment in learning and memory. Whereas this loss in neuroplasticity is gradual during normal aging, in neurodegenerative diseases such as Alzheimer’s disease, this loss is accelerated dramatically, leading to incapacitation of patients within a decade of onset of cognitive symptoms. The mechanisms that underlie this accelerated loss of neuroplasticity in Alzheimer’s disease are still not completely understood. While the progressively increasing proteinopathy burden, such as amyloid β plaques and tau tangles, definitely contribute directly to a neuron’s functional demise, the role of non-neuronal cells in controlling neuroplasticity is slowly being recognized as another major factor. These non-neuronal cells include astrocytes, microglia and oligodendrocytes, which through regulating brain homeostasis, structural stability, and trophic support, play a key role in maintaining normal functioning and resilience of the neuronal network. It is believed that chronic signaling from these cells affect the homeostatic network of neuronal and non-neuronal cells to an extent to destabilize this harmonious milieu in neurodegenerative diseases like Alzheimer’s disease. Here, we will examine the experimental evidence regarding the direct and indirect pathways through which astrocytes and microglia can alter brain plasticity in Alzheimer’s disease, specifically as they relate to the development and progression of tauopathy. In this review, we describe the concepts of neuroplasticity and glial plasticity in healthy aging, delineate possible mechanisms underlying tau-induced plasticity dysfunction, and discuss current clinical trials as well as future disease modifying approaches.